(untitled) (Advances in Oceanography and Limnology, 2015)
The construction of reservoirs and hydropower plants was accelerated in the past century due to the increasing aridity in many parts of the world. The effect of water regulations on the abundance of mosquito vectors is controversial. In this paper, the habitat preference of mosquitoes was investigated based on a 30-years long collection of the mosquito data in Hungary and military maps and satellite images. Three time phases of the analyzed section in the Danube River were analyzed in order to characterize the impact of human influence on mosquito habitats: the semi-natural phase, the post channelization phase and the post hydropower dam state. Geographical data referring to the years 1790, 1820, 1830, 1870, 1946 and 1955 were based on military maps, whereas the years 2004 and 2013 were analyzed by satellite imagery. The Amoros-like eupotamon A - plesiopotamon line represents an increasing gradient of habitat-suitability for mosquitoes. The habitat-preference of different mosquitoes to the Amoros-classified water habitats was based on a monographic collection data. This dataset contains the collecting and trapping results from the 1960s to the early 2000s in Hungary. We found that human-induced changes had prolonged impact on mosquito-suitable habitats, although the effect can be different for diverse mosquito species. The increase of the evenness of the mosquito fauna was seen since the mid-20th century, after the primary river regulation. The increasing areal extension of relatively warm and nutrient-rich water habitats had positive effects on the more rare members of the mosquito fauna, such as the potential malaria vector mosquito Anopheles algeriensis according to the model results. Summarizing, we found a strong, positive link between anthropogenic interventions and the mosquito diversity in water ecosystems.